Sexual Violence Prevention Strategies Based on Hadith Guidance - Abdul Wahid; Husna Amin; Jafar Assagaf; Agusni Yahya; Nufiar Nufiar (Universitas Islam Negeri Mataram, 2023)
Sexual violence continues to happen in different places and cannot be dealt with well. The rise in the rate of sexual violence from year to year is thought to be related to the state of education. So, many things about education need to be fixed to stop acts of sexual violence that have long-term effects. Handling cases of sexual violence is insufficient for punishing perpetrators because victims who have experienced violence cannot return to normal in their physical, psychological, or future conditions. More research, particularly on hadiths related to the prevention of sexual violence behavior, is required. In Islam, various strategies have been set up that are considered capable of saving the younger generation from sexual violence. Therefore, this article aims to present traditions related to efforts to prevent the prevalence of sexual violence in society. This study used a qualitative approach with a literature review model, and the data was analyzed using the fiqhul hadith approach. This approach is a method of understanding and interpreting Islamic jurisprudence based on the hadith of the Prophet Muhammad. The study discovers various strategies promoted by hadith to prevent sexual violence, such as managing the views of men's and women's genitals; managing educational institutions and gathering places that are separate for men and women; and promoting youth awareness to marry if they already have the ability to do so.